Two novel bombesin-like neuropeptides from the skin secretion of Pelophylax kl. esculentus: Ex vivo pharmacological characterization on rat smooth muscle types - Zhang, Luyao; Chen, Chen; Zou, Wanchen; Chen, Xiaoling; Zhou, Mei; Ma, Chengbang; Xi, Xinping; Chen, Tianbao; Shaw, Chris; Liu, Mingchun; Wang, Lei (Frontiers in Molecular Biosciences, 2022)
Mammalian bombesin-like neuropeptides (BLPs) play an important role in the regulation of physiological and pathophysiological processes. Frog skin-derived BLPs, of smaller size and diverse length and sequences at their N-terminus, have attracted the attention of many researchers. However, these N-terminal variants and the receptors modulating their pharmacological actions, are poorly studied and less understood. In this study, two BLPs, namely [Asn3, Lys6, Thr10, Phe13]3-14-bombesin and [Asn3, Lys6, Phe13]3-14-bombesin with primary structure NLGKQWATGHFM and NLGKQWAVGHFM, were isolated from the skin secretion of hybrid Pelophylax kl. esculentus. Both BLPs share similar primary structure with only a single amino acid substitution at eighth position (Threonine to Valine), while have quite different myotropic potencies. They exhibited contractile effects on rat urinary bladder and uterus ex vivo smooth muscle preparations in a dose-dependent manner with EC50 values in the range of 22.64 nM to 83.93 nM. The potency of [Asn3, Lys6, Thr10, Phe13]3-14-bombesim was approximately 3-fold higher to [Asn3, Lys6, Phe13]3-14-bombesin. Through the investigation of receptor selectivity using canonical bombesin receptor antagonist , it was found that [Asn3, Lys6, Thr10, Phe13]3-14-bombesin and [Asn3, Lys6, Phe13]3-14-bombesin had an affinity to both BB1 and BB2 receptors. Their contractile functions mainly modulated by both BB1 and BB2 receptors on rat urinary bladder and BB2 alone on rat uterus smooth muscle preparations. These data may provide new insights into the design of potent and selective ligand for the bombesin receptors. Moreover, [Asn3, Lys6, Thr10, Phe13]3-14-bombesin and [Asn3, Lys6, Phe13]3-14-bombesin did not induce significant haemolysis and toxicity to human normal cells, suggesting that these two natural novel BLPs have great potential for development into new drug candidates.